Unraveling the connection between gut microbiota and Alzheimer’s disease: a two-sample Mendelian randomization analysis - Zeng, Huiqiong; Zhou, Kaixia; Zhuang, Yu; Li, Aidong; Luo, Baiwei; Zhang, Ye (Frontiers in Aging Neuroscience, 2023)
Purpose Studies have shown a close relationship between gut microbiota (GM) and Alzheimer’s disease (AD). However, the causal relationship between them remains unclear. Methods We conducted a genome-wide association study (GWAS) using publicly available summary statistics data for GM and AD. We extracted independent genetic loci significantly associated with GM relative abundances as instrumental variables based on predefined thresholds (p < 1*e−5). The inverse variance-weighted (IVW) method was primarily used for causal relationship assessment. Additional analyses, including MR-Egger, weighted median, simple mode, and weighted mode, were performed as supplementary analyses. Results IVW analysis revealed significant correlations between certain microbial taxa and the risk of AD. Higher abundances of Actinobacteria at the class level, phylum. Actinobacteria, class. Deltaproteobacteria, order. Desulfovibrionales, genus. Oscillospira, and genus. Ruminococcaceae UCG004 (p < 0.048) was found to be positively associated with an elevated risk of AD. However, within the genus-level taxa, Ruminococcus1 (p = 0.030) demonstrated a protective effect on lowering the risk of AD. In addition, to ensure the robustness of the findings, we employed Cochrane’s Q test and leave-one-out analysis for quality assessment, while the stability and reliability of the results were validated through MR-Egger intercept test, MR-PRESSO global test, and sensitivity analysis. Conclusion This study provided a comprehensive analysis of the causal relationship between 211 GM taxa and AD. It discerned distinct GM taxa linked to the susceptibility of AD, thereby providing novel perspectives on the genetic mechanisms governing AD via the GM. Additionally, these discoveries held promise as valuable biomarkers, enabling the identification of potential therapeutic targets and guiding forthcoming AD investigations.